1983
DOI: 10.1007/bf02011578
|View full text |Cite
|
Sign up to set email alerts
|

Effect of litter nitrogen on decomposition and microbial biomass inSpartina alterniflora

Abstract: The effect on decomposition of 4 different levels of nitrogen in aerial tissue ofSpartina alterniflora, collected at the end of its growing season litter, was studied in laboratory percolators for 56 days at 20‡C. The CO2 evolution and the release of organic nitrogen and organic carbon were monitored. From these data, the ash-free dry weight (AFDW), nitrogen (N) content, and carbon∶nitrogen (C/N) ratio were calculated at various times during decomposition. Fungal biomass, bacterial biomass, and the relative au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
26
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(29 citation statements)
references
References 28 publications
3
26
0
Order By: Relevance
“…Furthermore, the bacteria would most likely have to derive its nutrition from a source other than S. alterniflora, since heterotrophic bacteria apparently do not differ greatly in isotopic composition from that of their carbon source (Fry & Sherr 1984, Blair et al 1985 Schwingharner ct d. (1983) reporled ihai bacterial biomass contributed 1.3 % to the total sedimentary carbon. Marinucci et al (1983) found a total microbial carbon content of 2.6 % of total carbon in aerobically degraded S. alterniflora litter. Therefore, it is unlikely that such a small standing stock of bacterial carbon per se could influence the isotopic composition of SOM.…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the bacteria would most likely have to derive its nutrition from a source other than S. alterniflora, since heterotrophic bacteria apparently do not differ greatly in isotopic composition from that of their carbon source (Fry & Sherr 1984, Blair et al 1985 Schwingharner ct d. (1983) reporled ihai bacterial biomass contributed 1.3 % to the total sedimentary carbon. Marinucci et al (1983) found a total microbial carbon content of 2.6 % of total carbon in aerobically degraded S. alterniflora litter. Therefore, it is unlikely that such a small standing stock of bacterial carbon per se could influence the isotopic composition of SOM.…”
Section: Discussionmentioning
confidence: 91%
“…The lignocelluloses from these herbaceous plants were mineralized several times faster than that from the hardwood, R. mangle. In various studies of the relationship between biodegradability of lignocellulosic material and chemical composition, lignin content (Cromack 1973;Fogel and Cromack 1977) and nitrogen content (Godshalk and Wetzel 1978;Marinucci et al 1983) are often highly correlated with biodegradability. Melillo et al (1982) found that the mass of hardwood leaf litter remaining in litter bags in the Hubbard Brook Experimental Forest after 1 year was more highly correlated with initial lignin-to-nitrogen ratios of leaf material than with lignin or nitrogen content alone.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of nitrogen is presumably due to stimulation of microbial activity (Witkamp 1966, Satchel1 & Lowe 1967, Harrison 1982, Marinucci et al 1983. The effect also may be the result of an interaction with phenolic compounds.…”
Section: Introductionmentioning
confidence: 99%